ASPEK MORAL TOKOH UTAMA DALAM NOVEL CONVENIENCE STORE WOMEN KARYA SAYAKA MURATA - Ella Nuraini (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study discusses the moral aspects of the main character in the novel convenience store women by Sayaka Murata with a semiotic review. The structure contained in the novel describes the form and meaning of the moral aspects which include divine morals, philosophical ideology morals, moral ethics and morals of legal discipline. The type of research used is descriptive qualitative. The data is in the form of data in the form of excerpts of expressions containing moral values contained in the novel. The novel Convenience Store Women by Sayaka Murata was used by researchers as a data source. The data collection technique used in this study is a note-taking technique. Data analysis techniques are descriptive analysis and content analysis. The moral aspects of the main character in the novel convenience store women by Sayaka Murata are the structure contained in the novel includes, a) the theme: a minimarket girl named Keiko to become normal b) characterization: the main character is Keiko and the main character there are many assistants such as Sugawara, Izumi, Mother, Father, Little sister, Dat-Kun, Iwaki, Yukari, Manager, Shiraha c) plot: mixed flow, namely forward and backward flow d) lattar/setting: setting where mostly in minimarkets and the cashier desk, time settings include morning, afternoon, evening, and evening, and atmosphere settings include tense, happy, chaotic, anxious/confused, and e) point of view: the first persona is me, which is shown by Keiko's character.